Application of Red and Blue LED Light on Cultivation and Postharvest of Tomatoes (Solanum lycopersicum L.) - Abdullah Bin Arif; Agus Budiyanto; null Setiawan; Tri Cahyono; Tri Ratna Sulistiyani; Tri Marwati; Siti Mariana Widayanti; null Setyadjit; Lamhot Parulian Manalu; Himawan Adinegoro; Nenie Yustiningsih; Mulyana Hadipernata; et al. (Scientifica)
Currently, light-emitting diode (LED) technology has produced a more energy-efficient and versatile technology as an artificial lighting system that can be applied in the agricultural sector. Artificial lighting technology has been proven to be effective in increasing the production of agricultural products, especially horticultural commodities. As one of the primary horticulture commodities, tomatoes are the most common crop produced in controlled environments with LED artificial lighting. The focus of this study is to describe the application of LED lights in tomato cultivation and postharvest. We provide an amalgamation of the recent research achievements on the impact of LED lighting on photosynthesis, vegetative growth, flowering, production, and postharvest of tomatoes. Red-blue (RB) lighting induces photosynthesis; increases the content of chlorophyll a, chlorophyll b, and carotenoids in tomato leaves; regulates vegetative growth in tomatoes; and increases the production of tomatoes. In postharvest tomatoes, blue LED lighting treatment can slowly change the color of the tomato skin to red, maintain hardness, and increase shelf life. Future research may be carried out on the effect of LED artificial lighting on tomatoes’ phytochemical, antioxidant and other crucial nutritional content. Different LED wavelengths can be explored to enhance various bioactive compounds and health-promoting components.